A construção das relações entre os estudantes no ensino à distância: análise e proposições pelo viés do Design Estratégico - Ribeiro, Cristiano Clezar (Universidade do Vale do Rio dos Sinos, 2013)
The current study assesses the view that the student in distance learning course presents when it comes to developing its relations with other participants – in the same course - that share this virtual environment, discussing how these perceptions are linked with the main concepts of Strategic Design. The selected universe for this research focuses the Specialization in Teaching for Professional Education, held at Senac-RS in 2010, the DL modality. For this research, the methodological procedures that have been adopted were the bibliographical research, electronic documentary research and structured interview through an electronic form sent to the students of the Teaching Expertise for Professional Education course. As a result of the crossing of the insights gained in the interview, one can point mainly for the development of relationships between students, that: (1) even with the coexistence online students still feel the need to meet in order to complement the development of relations, (2) students who have already made other courses in distance learning mode and students who live in the interior of the state established better relationships with colleagues, (3) it was noticed that there is a relationship between identity construction and development of virtual relationships. This research suggests that one can develop an integration of the virtual learning environment of the course (Moodle) with the social networking site Facebook. In addition to this, it is believed that the promotion of face meetings can be added to the system-product of the course, adding value by means of the relationships established in this environment.
Keywords: Design Estratégico; Sistema-produto; Educação a distância; Relações virtuais; Identidade virtual; Strategic Design; System-product; Distance learning; Virtual relationships; Virtual identity; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial